Crop breeding: exploiting genes for food and feed - Saleh, Ghizan (Universiti Putra Malaysia Press, 2009)

(untitled)
Crop breeding has contributed significantly to the increase in world food and feed productivity. It has evolved from selection efforts for better plants during early human domestication of crops, to classical breeding, and presently to modern marker assisted breeding. Crop breeding is conducted on the principle of Mendelian genetics, exploiting genes and genetic variations for traits to be improved through manipulation of the available genetic resources or introgression of genes from introduced materials. Significant impact of crop breeding has been seen in the development of food crop varieties including wheat, rice, maize and soybeans. The Green Revolution which was instrumented by Norman Borlaug, the Nobel Laureate for Agriculture, is a classic example of the meaningful contribution of crop breeding in alleviating famine and food shortages in the rapid population growth scenario. Through long years of systematic crop breeding efforts, significant achievements have been made in polyploid breeding, mutation breeding, hybrid breeding, molecular assisted breeding and breeding through genetic engineering. Hybrid breeding has revolutionised the breeding methods of maize, where single cross, double cross as well as three-way cross hybrids have been utilised in the industry, although single crosses are presently almost solely used for production. Food crop breeding efforts in Malaysia have seen the successful development of superior varieties of rice, maize, papaya, pineapple and banana, while breeding successes in oil palm and rubber have also been well realized. Maize breeding work conducted at Universiti Putra Malaysia has focused on grain maize for animal feed, as well as sweet corn for human consumption. The current grain maize breeding programme at UPM was initiated in 1987 with the acquisition of germplasm from foreign countries. These germplasm materials, together with the locally available varieties, were subjected to a recurrent selection programme employing both half-sib and full-sib selection methods. Concurrently, inbred lines were developed from these populations through continuous self pollinations and tests of combining ability. Selected inbred lines were utilized in diallel crosses, and subsequently, single crosses, double crosses and three-way crosses were developed and then tested for performance in replicated trials. After repeated evaluation at various selected locations and large scale plantings, the F1 hybrid variety Putra J-58 was released in 1998, with high yield, uniformity and possessing high grain nutritional quality. The locally developed inbred lines were then further involved in crosses with introduced lines from Indonesia and acid soil tolerant lines from CIMMYT, in efforts to develop hybrids that are tolerant to acid soils which make up 72% of the arable lands in Malaysia. SSR molecular markers were also used to assist in the selection of suitable cross combinations, and promising hybrids are expected to be released in the near future. The present sweet corn breeding work at UPM was initiated in 1990, with the application of recurrent selection on the local varieties, Manis Madu and Bakti-1. This led to the development of improved populations which were subsequently utilized in crosses with the modern hybrid varieties introduced from other countries. Subsequently, more cycles of recurrent selection for fresh ear yield, ear length and eating quality were imposed. The resulting improved populations were then utilized in breeding programmes introgressing genes from Ethiopian synthetic varieties, leading to the development and release of the synthetic variety, Putra GS-2002 in 2003, with superior fresh ear yield and taste quality. Along the way, inbred lines were developed from various local and imported genetic resources, for the purpose of hybrid variety development. Presently, these inbred lines are approaching complete homozygosity and awaiting combining ability analysis for production of hybrid varieties. Molecular assessment utilising SSR markers are also being used to predict performance of the inbred lines in hybrid combinations. As a design science, crop breeding is a long term effort, and therefore requires long term research funding and strategies to increase success in developing new varieties to meet the changing human needs and climatic conditions.